استخدام وسيلة الألغاز المتقاطعة لترقية التحصيل الدراسي للغة العربية دراسة تجربية لطلاب الصف العاشر في المدرسة الثانويّة الإسلامية الاهلية "الأشعري" كوراس ديويك جومبانج (Bilingua, 2023)
his article discusses the use of crossword puzzle media to Timprove the learning outcomes of grade 10 students at Madrasa Aliyah Al-Asy'ari Keras. This research aims to; (1) To find out the crossword puzzle media for students of class Xmadarsah aliyah Al-Asy'ari Keras in Jombang. (3) To find out whether the crossword puzzle media has an effect or not on the learning outcomes of class X students of Al-Asy'ari Islamic High School in Keras, Jombang. The method used is quantitative with observation, tests and interviews which are then analyzed using the man whitey test. As for the results of this study: (1) at school the teacher uses several learning media that are used in Arabic lessons, one of which is crossword media which is used to increase student understanding in learning Arabic. (2) the increase in learning outcomes is seen in the four skills in learning Arabic: listening skills, speaking skills, reading skills, writing skills. (3) the crossword puzzle media has an effect on improving student learning outcomes in Arabic lessons. This is addressed by the test results from the Man Whitney test with a sig signal, 0.000 <0.005